Interior and up to the boundary regularity for the fractional g-Laplacian: The convex case. (October 2022) - Fernández Bonder, Julián; Salort, Ariel; Vivas, Hernán
Abstract: We establish interior and up to the boundary Hölder regularity estimates for weak solutions of the Dirichlet problem for the fractional g − Laplacian with bounded right hand side and g convex. These are the first regularity results available in the literature for integro-differential equations in the context of fractional Orlicz–Sobolev spaces.